1989
DOI: 10.1007/bf01795359
|View full text |Cite
|
Sign up to set email alerts
|

Bovine spermatozoa as anin vitro model for studies on the cytotoxicity of chemicals: effects of chlorophenols

Abstract: The suitability of ejaculated bovine spermatozoa as an in vitro model for the assessment of the cytotoxic potential of chemicals was evaluated using several endpoints: swimming activity, adenine nucleotide content, membrane integrity and oxygen consumption. A series of chlorophenols inhibited sperm motion (motility and velocity) in a concentration-dependent manner. This could be determined quantitatively and reproducibly by means of videomicrography and automatic computer image analysis. The sperm immobilizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…In addition to conventional semen parameters motion activity of the spermatozoa was analysed using computerassisted videomicrography. The equipment employed (Brunner, Munnich, Germany) represented an advanced version of the system described previously (Seibert, 1988;Seibert et al, 1989). The following parameter settings for computer analysis were used in the present study: number of frames analysed: 16; sampling frequency: 25 Hz; minimal number of frames for classification: 9; cell size range: 5-30 pixels; linear velocity threshold: 10 pm s-'.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to conventional semen parameters motion activity of the spermatozoa was analysed using computerassisted videomicrography. The equipment employed (Brunner, Munnich, Germany) represented an advanced version of the system described previously (Seibert, 1988;Seibert et al, 1989). The following parameter settings for computer analysis were used in the present study: number of frames analysed: 16; sampling frequency: 25 Hz; minimal number of frames for classification: 9; cell size range: 5-30 pixels; linear velocity threshold: 10 pm s-'.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 summarizes the range of in vitro and in vivo bioassays currently available for reprotoxicity testing of ART products. These reprotoxicity bioassays test the possible negative influence on the reproductive mechanisms and processes like maturation, motility, and fertilization of mammalian spermatozoa and oocytes of mice, hamsters, rabbits, and bovine (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Exposed mouse embryos are being cultured in vitro or transplanted in vivo to test their developmental potential (14,18).…”
mentioning
confidence: 99%
“…In vitro methods to assess the potential cytotoxic effects of chemicals would be faster and cheaper than toxicology tests utilizing animals and would be in concert with present societal attitude towards animal welfare, since animal use would be greatly reduced. Sperm motility is inhibited or altered by a variety of chemicals, and in vitro chemical cytotoxicity studies with bull spermatozoa have demonstrated a correlation between chemically induced motility inhibition and endpoints of assays that measure cell death (Petzoldt et al, 1985;Seibert et al, 1989;Kemp et al, 1990). These previous studies how-ever, have made no attempts to produce a motion derived toxicological endpoint.…”
Section: Introductionmentioning
confidence: 99%